Transformações contemporâneas, impactos na formação do profissional no campo do direito : um estudo de caso na UFS (2001-2005) - Anjos, Ana Paula Machado dos (2008)
The purpose of this research is to bring a historic and gender perspective at the impact of technological and organizational innovations on the training of faculty teaching professionals in the field of legal studies. A study case was carried out among the teaching staff at the Universidade Federal de Sergipe Law School, which included a review of literature, semistructured interviews, historical documents and statistics. Our findings point at the impact of globalization on the process of professional training of law teachers, who are required increasing efforts connecting theory to practice, specially regarding the contributions of gender theory to the training and construction of legal studies oriented careers. Restructuring the pedagogic project of teaching professionals in the legal field so as to include gender perspectives, new technologies and a reflection on the social role of Law in the current world is a deeply felt urgent need.